A novel ECG criterion to differentiate left from right ventricular outflow tract premature complex. (3rd May 2020) - Nikoo, Mohammad Hossein; Taheri, Somayeh; Attar, Armin
Abstract: Objectives . Catheter ablation is an effective method in the treatment of idiopathic ventricular arrhythmias. The mapping methods used for predicting the original site of arrhythmias are difficult to use and time-consuming. Consequently, developing methods using surface ECG for guiding the location is important. Here, we have tested a new ECG criterion to differentiate the left from the right ventricular originated complexes (PVCs) or tachycardias (VTs). Designs . Sixty patients with idiopathic PVC or VT who had undergone a successful radiofrequency catheter ablation (RFA) of arrhythmia were enrolled. The surface ECG during sinus rhythm and arrhythmia was analyzed. Initial r wave Surface Area (ISA) index was measured by multiplying the R wave duration in milliseconds by the R wave amplitude in terms of millivolt in V1 or V2 leads. Results . Thirty-seven patients with right ventricular (RVOT) and 23 with left ventricular outflow tract (LVOT) originated VT or PVC were enrolled. The ISA index was significantly greater in LVOT-VT/PVC compared to RVOTs (63.6 ± 78.9 vs. 8.3 ± 7.3, p  < .001). With a cut off value of ≥15, the index could differentiate a left from right arrhythmia with 94.6% specificity and 78.2% sensitivity (Area on the curve, 0.81; p  < .001). Compared to other previously reported indices, ISA is the most specific one. Conclusion . ISA index can serve as a very useful ECG criterion for differentiating a LVOT- from RVOT-originated VTs or PVCs.